Analysis of Investment Feasibility in Marketing Information System Acquisition - Ibnul Mufadlol, Abdurrohman; Akbar, Mhd. Furqon (Manajemen Bisnis, 2024)
Information technology plays a significant role in spreading information fast and efficiently. PT.KMB, as one of the companies that focuses on the usage of technology as its operation, acquired the Information Marketing System based on WhatsApp from WS. This research is aimed to evaluate the stated acquisition investment feasibility. The research method used is quantitative descriptive and focuses on the financing aspect. The three investment feasibility evaluation criteria used are Net Present Value (NPV), Payback Period (PP), and Profitability Index (PI). Data that can be analyzed includes PT.KMB income and expenses from June 2022 until October 2023. The result shows that NPV from the stated acquisition valued at Rp139.551.205, indicates a positive outcome with an increase in income of 20% per year. The Payback Period is estimated to happen in 1.2 years or 15 months, whereas Discounted Payback Period is 1.12 years or 13 months. In addition, the value of the Profitability Index (PI) in the amount of 1.4 shows that the stated acquisition is feasible to be implemented.